Os limites à delegação do exercício do poder de polícia estatal: análise sobre a possibilidade de atuação dos particulares - Ariane Shermam Morais Vieira (2016)
Administrative Law has been going through several intense transformations in the last couple of decades, especially during the second half of the XX century. In Brazil, it has been observed that these transformations, which came into effect with the Constitution of 1988, have allowed the State to be more open to the participation of citizens with the attainment of public interest. On the other hand, they have revealed an intense search from the State for partnerships, in a broad sense, with these same citizens, so that to promote procurement of collective interest, adding to this the tendency of the reinterpretation of the administrative legal system, and consequently, the performance of administrative functions, so to distance it from an authoritative conception. This context has given, to the doctrine as well as to the Brazilian jurisprudence, the discussions about the possibility of the State to delegate to the private sector the exercise of judicial acts of police power. This pertains to State owned activities that, summarized, seek to adjust the exercise of liberty and citizen owned property to the interest of all. Currently, the major understanding, not only in doctrine but also in jurisprudence, is that the legal acts of police power are non-delegable to the private sector. Attributed to this non-delegability is, among other arguments, the impossibility to attribute to the private sector the task of performing certain public powers over one another, for the risk of violating equality. On the other hand, understandings that defend a partial delegation of police power have arisen, while others, in smaller proportions, argue in favor of a wider delegation of this State activity. In this context, this paper will seek to evaluate if the delegation of police power finds support in the Constitution of 1988, as well as to verify the limits and conditions of this delegation. This way, one can verify that the delegation of determined judicial acts concerning the police power is possible, as long as this transfer does not bring the manifestation of ample decision powers or the coercion of private citizens upon one another.